The Use of Dirac Oscillator as Medium Substrate for Quantum Heat Engine - Heru Sukamto; Bintoro Anang Subagyo; Agus Purwanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2022)
The research on Dirac oscillators has been increasing recently. In this paper, a quantum heat engine by means of a Dirac oscillator that interacts with the external magnetic field is proposed. Relativistic Landau energy levels are used to perform the iso-energetic cycle. The large magnetic field is set to obtain a perfect thermodynamic cycle. Some stable performances at a certain magnitude of magnetic field and expansion parameter range are obtained. When the value of efficiency is compared with the non-relativistic case, an opposite result occurs. Therefore, a quantum heat engine using a Dirac oscillator doesn’t govern like a classical oscillator.